Characterisation of Lactococcus lactis M4 carrying dual-expression plasmid to demonstrate bactofection of human colon cancer cell line, SW620 - Faroque, Habibah (2017)
Lactic acid bacteria (LAB) such as Lactococcus lactis is a well-known foodgrade bacterium which is identified as an excellent candidate for delivering DNA vaccine towards colorectal carcinoma cells. Safety usage of L. lactis was confirmed by its generally recognised as safe (GRAS) status and the long tradition of use in the food industries. Exploitation of LAB as probiotics also provided an interesting and broad field of possibilities in overcoming boundaries towards biomedicine markets. This is because the production cost is affordable even in large scale production. Implementation of gene therapy for cancer recovery such as immunotherapy has become an attractive and an alternative approach towards classical treatments. Most of the immunotherapeutic studies have been using delivery vectors such as viruses, attenuated pathogens and parasites as they efficiently deliver plasmids or DNA towards various types of cancer cells. However, researcher questioned on the possibility of these vectors to revert back its pathogenicity has become one of the hurdles for this research to be put into practice. Therefore, LAB with its GRAS status has shown to be a better alternative vector for gene delivery. In this study, a local dairy isolate, L. lactis M4 was investigated for its ability to be developed as a live delivery vector of plasmid DNA harboring the fluorescent genes towards the human colon cancer cell line, SW620. The interaction mechanisms involved between this LAB strain and SW620 during the interaction assays was analysed. This human colorectal cell was used in this study since it is an epithelial cell which is suitable to be used as an expression host that would allow for the demonstration of the plasmid delivery into the mammalian cells. In addition, the SW620 cells have also been widely used for the application in cancer research involving LAB. It was shown, through the trypan blue exclusion method performed along with the interaction assays that L. lactis M4 has no cytotoxicity effect towards SW620 cells at the multiplicity of infection (MOI) of 250:1 and below. L. lactis M4 strain was found to adhere and to internalise into the SW620 cells optimally at two hours postinfection at the MOI 250:1, bacteria per cancer cell and managed to survive intracellularly for 7 hours. When SW620 cells were pre-incubated with Cytochalasin D and Vinblastine drugs (the microfilaments and microtubules destabilisers) before the invasion assays, uptake of the L. lactis M4 was blocked indicating that the mode of delivery into the cell was via endocytosis which are dependent on the rearrangement of both microfilament and microtubule. Bactofection mechanism of the SW620 cells by L. lactis M4 was demonstrated through the 3D image modeling of the expression of fluorescent reporter proteins from a dual-expression plasmid, pHSR constructed in this study. Viable L. lactis M4 was found to express red fluorescent protein (RFP) in the intracellular compartment of the SW620 cells at three hours postinfection. Concurrently, SW620 cells were also observed to express green fluorescent protein (GFP) at the same time. Hence, the success of gene delivery demonstrated based on the expression of RFP and GFP from pHSR have proven that L. lactis M4 can be considered as a promising candidate of a live delivery vector of plasmid DNA into the mammalian cells.